Pergeseran Perilaku Sosial Laki-laki dalam Kegiatan Sosial - Rahmat Danil; Fatmariza Fatmariza; Junaidi Indrawadi (Journal of Civic Education, 2019)
ABSTRACT This research aim to describe changes in male social behavior, causal factors and efforts to increase men's awareness in social activities. This study uses a qualitative approach conducted in Nagari Singgalang Kecamatan X Koto. The research subjects were wali nagari, public figure, adult male and youth. Data was collected through interviews, observation and documentation, which tested its validity through source triangulation and method triangulation.